Pengaruh Pemberian Ultrasound Dan Terapi Latihan Hold Relax Terhadap Penurunan Nyeri De Quervain Syndrome Di Rumah Sakit Al Islam Bandung - Muhammad Fakhri Fadhlullah; Sulaiman Sulaiman; R. Eko Legstyanto (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Without realizing it, humans use their limbs excessively and with the repetitive rhythm of the many existing human body members, the hands and thumbs are body parts that are often used repeatedly for long periods of time. One of the disorders caused by excessive movement is De Quervain Syndrome which is a disorder that causes inflammation and is accompanied by pain. Objective: This study was to determine the effect of giving ultrasound modality and holdrelax exercise therapy on the condition of de Quervain syndrome. Research method: pre-experimental design research method with one group pretest-posttest design There are 20 research samples of which 12 are women, 8 are men. The selected sample was also using a purposive sampling technique at Al Islam Hospital Bandung. Results: the value of sig 2 tailed 0.000 Wilxocon means that there is a difference in values before and after the administration of ultrasound modality and hold relax therapy in de quervain conditions using the Shapiro Wilk normality test because of 30 samples, while the significant value shows 0.000 which means that the result is a significant value of 0.05 then the hypothesis is accepted. Conclusion: there is an effect on giving modalities and exercise therapy to reduce pain.Keywords: Ultrasound modalities, Exercise Therapy